A new genus of palms, Neosalacca (Arecaceae, Calamoideae, Calameae, Salaccinae) - Henderson, Andrew; Kuhnhäuser, Benedikt G. (Phytotaxa, 2026)
Phylogenetic analysis of molecular data from species within subtribe Salaccinae resolved three well-supported clades, and these are also supported by morphological data. Two of these clades have been recognized previously at the generic level, Eleiodoxa and Salacca. Here, the third clade is described as a new genus, Neosalacca.